Condylomata acuminata in children: report of four cases. - Sait, M A (1985)
Four cases of condylomata acuminata in children (two boys, two girls) are reported. Three children had perianal warts and one vulvar warts. One of the four children had been sexually assaulted, but a history of sexual contact was absent in the other three. Surgical excision was undertaken in one case and the others responded well to the local application of 25% podophyllin in benzoin tincture compound. In the absence of sexual contact, a non-coital mode of transmission of infection could be a possibility.